IMPLEMENTATION OF BOARDING-BASED FORMAL SCHOOL LEARNING AT SYUBBANUL WATHON HIGH SCHOOL TEGALREJO MAGELANG - Shifa, Tafrihatush; Zafi, Ashif Az; Ambarwati, Susi; Romadhona, Muhammad Arsyada; Nada, Fina Qothrun (ANDRAGOGI, 2024)
Modern developments have made changes in the world of education, one of which is combining the formal school education system which uses the national curriculum and the Islamic boarding school education system which uses the local curriculum. This research aims to increase knowledge about the Islamic boarding school-based high school learning system which is currently rarely implemented in the Indonesian education system. This research uses qualitative methods, namely data collection methods through interviews and observations as well as through library sources, scientific journal articles and books. This research discusses the integration of the formal school education system and the Islamic boarding school education system at Syubbanul Wathon High School.  The process of accepting new students requires applicants to take general knowledge tests such as English, Indonesian and Mathematics, as well as a reading and writing test of the Al-Qur'an. The implementation of learning is divided into 2, namely male students study from morning to afternoon and afternoon to evening reciting the Koran at the boarding school, while female students do the opposite. Then in the evening the santri and female students continue to recite the Koran at the Islamic boarding school. Learning evaluation is carried out by combining all assessments at school and at the Islamic boarding school.  A learning system like this can balance students' religious knowledge and general knowledge, so that there will be no gaps in one of them.